Preparation method of quantum dot / metal organic framework-based composite material, material and application of quantum dot / metal organic framework-based composite material

By forming g-C3N4 quantum dots in situ on NH2-UiO-66 nanocrystals to form a composite nano reactor, the photocatalytic degradation technology is used to solve the problem that traditional methods are difficult to remove high concentrations and difficult to degrade organic pollutants, achieving high efficiency, Environmentally friendly pollutant degradation effect.

CN119425801APending Publication Date: 2025-02-14JILIN NORMAL UNIV

Patent Information

Application Number
CN202411650095.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove high concentrations of difficult-to-degrade organic pollutants, and traditional treatment methods have problems such as high energy consumption, complex processes, inability to completely degrade or mineralization.

Method used

Using the preparation method of quantum dot/metal organic framework composite materials, g-C3N4 quantum dots are uniformly deposited on NH2-UiO-66 nanocrystals by in-situ forming g-C3N4 quantum dots to form spherical nanoreactors, and photocatalytic degradation technology is used to improve pollutants. Degradation efficiency.

Benefits of technology

The photocatalytic degradation ability of tetracycline and other difficult-to-degrade pollutants is significantly enhanced under visible light irradiation, the adsorption property of the catalyst and the separation efficiency of photogenerated electron holes are improved, and the catalyst is easy to recover and has recycling value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425801A_ABST
    Figure CN119425801A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a composite material based on quantum dots / metal organic frameworks, the composite material and application of the composite material, and belongs to the technical field of preparation and application of nanometer materials, and the composite material based on the quantum dots / metal organic frameworks is a g-C3N4 QDs / NH2-UiO-66 composite material with visible light response. The g-C3N4 quantum dots formed in situ are deposited on NH2-UiO-66 nanocrystals to form a spherical nanoreactor, and degradation products with high biodegradability and low toxicity are generated through photocatalytic degradation. Compared with pure g-C3N4 QDs and NH2-UiO-66, the g-C3N4 QDs / NH2-UiO-66 composite material has the advantages that the capability of photocatalytic degradation of tetracycline under the irradiation of visible light is obviously enhanced; the separation efficiency is improved by increasing the number of photocatalytic active sites and delaying effective charge transfer recombination of photo-induced electron hole pairs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of nano material preparation and application, and specifically relates to a preparation method, material and application of a quantum dot / metal organic framework composite material. Background Art

[0002] The use of antibiotics has a strong inhibitory or bactericidal effect on various pathogenic microorganisms, which greatly ensures the orderly development of clinical medicine and animal husbandry. However, due to the negative impact of pharmaceutical active compounds on human health and the environment, their frequent appearance in water bodies and the associated environmental hazards have become a problem that needs to be solved urgently. Therefore, it is very important to develop various effective strategies and solutions to solve these problems.

[0003] Carbon nitride quantum dots (g-C3N4QDs) material is a semiconductor nanomaterial with a radius less than or close to the Bohr radius. It can receive excitation light to produce fluorescence. When it is reduced to a certain critical size, the movement of electrons in three-dimensional space is restricted, and it can show quantum confinement effect. Quantum confinement structure can show size-dependent electronic properties. The restricted electron movement leads to discrete atomic-like electronic structures and size-dependent energy levels. They have high adjustability in chemical, physical, electrical and optical properties, and have high leverage in material and device design. Among all modification methods, the construction of heterostructures with two or more semiconductor materials can integrate the advantages of multiple components, improve the efficiency of photogenerated charge separation, and maintain high redox ability of electrons and holes. Therefore, the photogenerated electrons and holes of a single-component photocatalyst are easy to recombine with each other, but it is easy to cause a serious reduction in the photocatalytic efficiency. As an important type of porous material, MOFs materials have adjustable pore size and modifiable pore surface, ultra-low density, ultra-high specific surface area, insolubility in common solvents, etc. compared with traditional porous materials such as zeolite, mesoporous silica and activated carbon, which makes them have good adsorption. Therefore, compounding it with a semiconductor photocatalyst can make the catalyst have good adsorption, and adsorb low-concentration and highly toxic pollutants in sewage on the surface of the semiconductor photocatalyst. At the same time, the good electron transmission ability of MOFs materials can further reduce the recombination rate of electrons and holes, thereby improving the photocatalytic degradation efficiency. According to research, to date, there has been no report on the spherical nanoreactor composed of in-situ formed g-C3N4 quantum dots uniformly deposited on NH2-UiO-66 nanocrystals.

[0004] Defects and shortcomings of the existing technology: At present, there are many methods for treating high-concentration refractory organic pollutants, including adsorption separation, micro-electrolysis technology, biofiltration, etc. However, these traditional treatment methods are often limited in practical applications of water pollution treatment due to high energy consumption, complex processes, and inability to completely degrade or mineralize organic pollutants. Among them, adsorption and photocatalytic degradation are considered to be the main methods for removing organic pollutants from air and water. Compared with photocatalytic degradation, it is a more thorough, green, and environmentally friendly remediation method. It can convert organic products into non-toxic substances under simple conditions without secondary harm to the environment. Moreover, the catalytic conditions are simple and can save a lot of energy, but the adsorption process generally only transfers pollutants from one phase to another, reducing the concentration of pollutants and cannot eliminate a large number of pollutants. Summary of the invention

[0005] The invention provides a preparation method, material and application of a quantum dot / metal organic framework composite material, wherein the quantum dot / metal organic framework composite material is a g-C3N4QDs / NH2-UiO-66 composite material responsive to visible light, and the preparation method comprises the following steps: S1: placing melamine in a crucible, heating and keeping it warm, then cooling it to room temperature, taking it out, grinding it, and obtaining the product g-C3N4 nanosheets; heating the g-C3N4 nanosheets, then adding mixed acid to perform ultrasonication, and obtaining a mixed solution; washing the mixed solution with deionized water, and transferring the obtained suspension to a reactor for heating, and obtaining a g-C3N4QDs solution; S2: Zirconium tetrachloride (ZrCl4) and 2-aminoterephthalic acid (H2ATA) are fully dissolved in 10-30 ml N,N-dimethylformamide (DMF), 1-3.6 ml acetic acid (HAc) is added, and the resulting mixed solution is transferred to a Teflon-lined autoclave for heating, then cooled to room temperature, and the product is collected by centrifugation at a speed of 8000 rpm, and the product is washed twice with DMF and ethanol, respectively, and vacuum dried to obtain NH2-UiO-66 particles; S3: Under ultrasonic conditions, NH2-UiO-66 particles are dispersed in ethanol, and then the g-C3N4QDs solution obtained in step S1 is added and stirred, and the obtained mixed solution is placed in a water bath and heated to obtain NH2-UiO-66 particles modified by g-C3N4QDs; The heating and heat preservation of melamine in step S1 is specifically: 2°C·min -1 Heat to 500-550℃ at a heating rate of 1000℃ and keep warm for 2-4 hours; The heating of the g-C3N4 nanosheets in step S1 is: 2°C·min -1 Heat to 400-500℃ at a heating rate and maintain for 1-2 h; The mixed acid in step S1 is concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1; The ultrasonic time in step S1 is 10-16 h; The suspension in step S1 is transferred to a reaction vessel and heated at a temperature of 200-300° C. for 10-15 h; The molar ratio of zirconium tetrachloride (ZrCl4) and 2-aminoterephthalic acid (H2ATA) in step S2 is 1:1-3; The heating temperature in step S2 is 100-120° C. and the heating time is 15-24 h; The vacuum drying temperature in step S2 is 50-60°C and the drying time is 20-24 h; The dosage ratio of NH2-UiO-66 particles and g-C3N4QDs solution in step S3 is 1 g:5-10 μL; The stirring time in step S3 is 20-24 h; The heating temperature in step S3 is 80-100°C.

[0006] The quantum dot / metal organic framework composite material is prepared by the above-mentioned preparation method.

[0007] An application of the above-mentioned quantum dot / metal organic framework composite material for degrading tetracycline (TC).

[0008] The beneficial effects of the present invention are: The technical problem to be solved by the present invention is to provide a novel and simple method for synthesizing a quantum dot / metal organic framework composite material, so that the material has better catalytic properties while maintaining its own adsorption properties; the synthesis method has the advantages of good repeatability, high yield and stable product performance. The present invention utilizes a spherical nanoreactor formed by uniformly depositing g-C3N4 quantum dots formed in situ on NH2-UiO-66 nanocrystals. Degradation products with high biodegradability and low toxicity are produced through photocatalytic degradation. Compared with pure g-C3N4QDs and NH2-UiO-66, the ability of the g-C3N4QDs / NH2-UiO-66 composite material to photocatalytically degrade tetracycline (TC) under visible light irradiation is significantly enhanced. The separation efficiency is improved by increasing the specific surface area (increasing the number of photocatalytic active sites) and delaying the effective charge transfer recombination of photogenerated electron-hole pairs; the catalyst is easy to recover and has recyclable value. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 XRD pattern of the g-C3N4QDs / NH2-UiO-66 composite material of the present invention; Figure 2TEM image of the g-C3N4QDs / NH2-UiO-66 composite material of the present invention; Figure 3 This is a photocurrent test comparison diagram of the g-C3N4QDs / NH2-UiO-66 composite material of the present invention, pure g-C3N4 and NH2-UiO-66; Figure 4 This is a comparison chart of the photocatalytic degradation experiments of tetracycline by the g-C3N4QDs / NH2-UiO-66 composite material of the present invention, g-C3N4QDs and NH2-UiO-66. DETAILED DESCRIPTION

[0010] Example 1 S1: Weigh 5 g of melamine and place it in a crucible at 2 °C min -1 The product g-C3N4 nanosheets were obtained by heating the sample to 500℃ at a heating rate of 2℃·min. -1 The mixture was heated to 400 °C at a heating rate of 100 °C and maintained for 1 h, placed in a mixed solution of 5 ml concentrated sulfuric acid and 5 ml concentrated nitric acid, and subjected to ultrasound for 10 h. The generated impurities were then washed with deionized water. The washed suspension was transferred to a suitable reactor, placed in an oven and heated to 200 °C for 10 h to obtain a g-C3N4QDs solution. S2: Zirconium tetrachloride (ZrCl4, 0.1 mmol, 0.0406 g) and 2-aminoterephthalic acid (H2ATA, 0.130 mmol, 0.0235 g) were fully dissolved in 10 ml N,N-dimethylformamide (DMF); then, 1.5 ml acetic acid (HAc) was added to the mixed solution and stirred vigorously to control the growth rate of nanoparticles; then the mixed solution was transferred to a 50 ml Teflon-lined autoclave, heated in an oven at 100 °C for 15 h, cooled to room temperature, and centrifuged at 8000 rpm to collect the product; then washed twice with DMF and ethanol respectively, and dried at 60 °C in vacuum for 20 h to obtain NH2-UiO-66; S3: Under ultrasonic treatment, 2 g of NH2-UiO-66 particles were dispersed in 1 ml of ethanol, and 20 μL of the g-C3N4QDs solution obtained in step S1 was added to the ultrasonically homogenized NH2-UiO-66 ethanol solution. The mixture was stirred for 24 h, and the mixed solution was placed in an 80°C water bath. The solvent was slowly evaporated until a solid product was formed. The prepared product was composed of NH2-UiO-66 particles modified with g-C3N4QDs, namely g-C3N4QDs / NH2-UiO-66, with a yield of up to 93%.

[0011] The XRD patterns of g-C3N4QDs / NH2-UiO-66 composites are shown in Figure 1 As shown, for g-C3N4QDs, there is an obvious typical diffraction peak at 27.8°, and this spectrum shows that the composite material prepared by the above method is successfully synthesized; Figure 2 In the TEM image, many tiny dot-like particles of about 2 nm can be observed on the surface of NH2-UiO-66, confirming the presence of surface-decorated g-C3N4QDs.

[0012] By transmission electron microscopy (TEM) ( Figure 3 ) It can be seen from the photocurrent test that after the g-C3N4QDs / NH2-UiO-66 sample is successfully composited, its photocurrent intensity is enhanced, the photocurrent density is increased, and the separation efficiency is optimal.

[0013] Example 2 S1: Weigh 10 g of melamine and place it in a crucible at 2 °C min -1 The temperature was raised to 525°C at a rate of 100 °C and maintained for 3 h. After cooling to room temperature, the product g-C3N4 nanosheets were taken out and ground. An appropriate amount of the ground g-C3N4 nanosheet sample was taken and heated at 2 °C·min -1 The mixture was heated to 450 °C at a heating rate of 1.5 °C and maintained for 1.5 h, placed in a mixed solution of 7.5 ml concentrated sulfuric acid and 7.5 ml concentrated nitric acid, and ultrasonicated for 12 h. The generated impurities were then washed with deionized water. The washed suspension was transferred to a suitable reactor, placed in an oven and heated to 230 °C for 12 h to obtain a g-C3N4QDs solution. S2: Zirconium tetrachloride (ZrCl4, 0.5 mmol, 0.203 g) and 2-aminoterephthalic acid (H2ATA, 0.520 mmol, 0.094 g) were fully dissolved in 20 ml N,N-dimethylformamide (DMF); 2.0 ml acetic acid (HAc) was added to the mixed solution and stirred vigorously to control the growth rate of nanoparticles; then the mixed solution was transferred to a 50 ml Teflon-lined autoclave, heated in an oven at 100 °C for 18 h, cooled to room temperature, and centrifuged at 8000 rpm to collect the product; then washed twice with DMF and ethanol respectively, and dried at 50 °C in vacuum for 24 h to obtain NH2-UiO-66; S3: Under ultrasonic treatment, 10 g of NH2-UiO-66 particles were dispersed in 5 ml of ethanol, and 60 μL of the g-C3N4QDs solution obtained in step S1 was added to the ultrasonically homogenized NH2-UiO-66 ethanol solution, and stirred for 24 h; the mixed solution was placed in a 90°C water bath, and the solvent was slowly evaporated until a solid product was formed; the prepared product was composed of NH2-UiO-66 particles modified with g-C3N4QDs, that is, g-C3N4QDs / NH2-UiO-66, with a yield of up to 92%.

[0014] Example 3 S1: Weigh 10 g of melamine and place it in a crucible at 2 °C min -1 The product g-C3N4 nanosheets were obtained by heating the sample to 550℃ at a heating rate of 2℃·min -1 The mixture was heated to 500 °C at a heating rate of 100 °C and maintained for 2 h, placed in a mixed solution of 10 ml concentrated sulfuric acid and 10 ml concentrated nitric acid, and subjected to ultrasound for 14 h. The generated impurities were then washed with deionized water. The washed suspension was transferred to a suitable reactor, placed in an oven and heated to 260 °C for 15 h to obtain a g-C3N4QDs solution. S2: Zirconium tetrachloride (ZrCl4, 1.0 mmol, 0.406 g) and 2-aminoterephthalic acid (H2ATA, 1.0 mmol, 0.235 g) were fully dissolved in 25 ml N,N-dimethylformamide (DMF); then, 3.0 ml acetic acid (HAc) was added to the mixed solution and stirred vigorously to control the growth rate of nanoparticles; then the mixed solution was transferred to a 50 ml Teflon-lined autoclave, heated in an oven at 120 °C for 20 h, cooled to room temperature, and centrifuged at 8000 rpm to collect the product; then washed twice with DMF and ethanol respectively, and dried under vacuum at 60 °C for 24 h to obtain NH2-UiO-66; S3: Under ultrasonic treatment, 15 g of NH2-UiO-66 particles were dispersed in 7.5 ml of ethanol; 120 μL of the g-C3N4QDs solution obtained in step S1 was added to the ultrasonically homogenized NH2-UiO-66 ethanol solution and stirred for 24 h; the mixed solution was placed in a 100°C water bath and the solvent was slowly evaporated until a solid product was formed; the prepared product was composed of NH2-UiO-66 particles modified with g-C3N4QDs, namely g-C3N4QDs / NH2-UiO-66, with a yield of up to 92%.

[0015] Example 4 S1: Weigh 10 g of melamine and place it in a crucible at 2 °C min -1 The product g-C3N4 nanosheets were obtained by heating the sample to 550℃ at a heating rate of 2℃·min -1 The mixture was heated to 500 °C at a heating rate of 100 °C and maintained for 2 h, placed in a mixed solution of 10 ml concentrated sulfuric acid and 10 ml concentrated nitric acid, and subjected to ultrasound for 16 h. The generated impurities were then washed with deionized water. The washed suspension was transferred to a suitable reactor, placed in an oven and heated to 300 °C for 15 h to obtain a g-C3N4QDs solution. S2: Zirconium tetrachloride (ZrCl4, 1.0 mmol, 0.406 g) and 2-aminoterephthalic acid (H2ATA, 1.0 mmol, 0.235 g) were fully dissolved in 30 ml N,N-dimethylformamide (DMF); then 3.6 ml acetic acid (HAc) was added to the above mixed solution, and the mixture was stirred vigorously to control the growth rate of the nanoparticles. Then the mixed solution was transferred to a 50 ml Teflon-lined autoclave, heated in an oven at 120 °C for 24 h, cooled to room temperature, and centrifuged at 8000 rpm to collect the product; then washed twice with DMF and ethanol respectively, and dried in vacuum at 60 °C for 24 h to obtain NH2-UiO-66; S3: Under ultrasonic treatment, 20 g of NH2-UiO-66 particles were dispersed in 10 ml of ethanol, and 200 μL of the g-C3N4QDs solution obtained in step S1 was added to the ultrasonically homogenized NH2-UiO-66 ethanol solution, and stirred for 20 h; the mixed solution was placed in an 80°C water bath, and the solvent was slowly evaporated until a solid product was formed; the prepared product was composed of NH2-UiO-66 particles modified with g-C3N4QDs, that is, g-C3N4QDs / NH2-UiO-66, with a yield of up to 93%.

[0016] Comparative Example Tetracycline (TC) is a representative pollutant of antibiotics. In order to investigate the degradation results, the pure g-C3N4QDs prepared in step S1 of Example 1, the NH2-UiO-66 prepared in step S2, and the g-C3N4QDs / NH2-UiO-66 were used to perform photocatalytic degradation experiments on tetracycline. Figure 4 It can be confirmed that the composite photocatalytic material g-C3N4QDs / NH2-UiO-66 has good degradation ability for tetracycline.

[0017] The above embodiments are only partial implementation schemes of the present invention, but the protection scope of the present invention is not limited thereto. The various aspects and implementation schemes of the present invention disclosed herein are only examples of specific ways to make and use the present invention. The present invention is not limited to any limitation due to the sequence and specific operations of the embodiments. Any replacement and changes that can be easily thought of by any researcher familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a quantum dot / metal organic framework composite material, characterized in that: The following steps are involved: S1: placing melamine in a crucible, heating it and keeping it warm, then cooling it to room temperature, taking it out, grinding it, and obtaining the product g-C3N4 nanosheets; heating the g-C3N4 nanosheets, then adding mixed acid to perform ultrasonication, and obtaining a mixed solution; washing the mixed solution with deionized water, and transferring the obtained suspension to a reactor and heating it, and obtaining a g-C3N4 QDs solution; S2: Zirconium tetrachloride (ZrCl4) and 2-aminoterephthalic acid (H2ATA) are fully dissolved in 10-30 ml N,N-dimethylformamide (DMF), 1-3.6 ml acetic acid (HAc) is added, and the resulting mixed solution is transferred to a Teflon-lined autoclave for heating, then cooled to room temperature, and the product is collected by centrifugation at a speed of 8000 rpm, and the product is washed twice with DMF and ethanol, respectively, and vacuum dried to obtain NH2-UiO-66 particles; S3: Under ultrasonic conditions, NH2-UiO-66 particles are dispersed in ethanol, and then the g-C3N4QDs solution obtained in step S1 is added and stirred. The obtained mixed solution is placed in a water bath and heated to obtain NH2-UiO-66 particles modified by g-C3N4QDs.

2. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: The heating and heat preservation of melamine in step S1 is specifically: 2°C·min -1 The heating rate is heated to 500-550°C and kept warm for 2-4 h; the heating of the g-C3N4 nanosheets is: at 2°C·min -1 Heat to 400-500 °C at a heating rate and maintain for 1-2 h.

3. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: The mixed acid in step S1 is concentrated sulfuric acid and concentrated nitric acid in a volume ratio of 1:1; and the ultrasonic time is 10-16 h.

4. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: The suspension in step S1 is transferred to a reaction vessel and heated at a temperature of 200-300° C. for 10-15 h.

5. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: The molar ratio of zirconium tetrachloride (ZrCl4) and 2-aminoterephthalic acid (H2ATA) in step S2 is 1:1-3.

6. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: In step S2, the heating temperature is 100-120° C., the heating time is 15-24 h, the vacuum drying temperature is 50-60° C., and the drying time is 20-24 h.

7. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: The dosage ratio of NH2-UiO-66 particles and g-C3N4 QDs solution in step S3 is 1 g:5-10 μL.

8. The method for preparing a quantum dot / metal organic framework composite material according to claim 1, characterized in that: In step S3, the stirring time is 20-24 h; the heating temperature is 80-100°C.

9. A quantum dot / metal organic framework composite material prepared by the preparation method according to any one of claims 1 to 8.

10. An application of the quantum dot / metal organic framework composite material according to claim 9 for degrading tetracycline.

Citation Information

Patent Citations

  • Method for treating organic wastewater by activating peroxymonosulfate with functionalized zirconium-based metal organic framework / protonated carbon nitride composite material

    CN110776049A

  • Preparation method of photocatalytic heterojunction nano composite material for removing algae in water body

    CN111389469A

  • Carbon nitride quantum dot / tungsten trioxide composite photocatalytic material and preparation method therefor

    WO2022077811A1

Cited By

  • Preparation method and application of molecularly imprinted cathode photoelectrochemical sensor based on CNQDs (at) CTP nanocomposite

    CN119985646A